Baseline correlations between [18F]GTP1 PET SUVR and MRI white matter hyperintensities in prodromal‐to‐mild Alzheimer's disease suggest independent contributions to cognitive impairment: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Manser, Paul T; Teng, Edmond; Pickthorn, Karen; Blendstrup, Mira; Anegondi, Neha; Krishnan, Anithapriya; Song, Zhuang; Carano, Richard A.D.; Keeley, Michael; Wildsmith, Kristin R; Weimer, Robby; Bohorquez, Sandra Sanabria
Abstract: Background: White matter hyperintensities (WMH) on MRI are commonly seen in Alzheimer's disease (AD) and thought to represent co‐morbid microvascular ischemic disease. However, the relationship between WMH and tau pathology in AD remains incompletely understood. We explored this question using screening/baseline data from a Phase 2 study of the anti‐tau antibody semorinemab (Tauriel; NCT03289143), which included both MRI and [ 18 F]GTP1 tau PET imaging. Method: Participants in the Tauriel study are aged 50‐80, meet criteria for AD dementia or mild cognitive impairment (MCI), have MMSE of 20‐30, global Clinical Dementia Rating (CDR) of 0.5 or 1, evidence of significant amyloid pathology, and significant episodic memory impairment (RBANS delayed memory index < 85), and undergo screening MRIs, with WMH quantified using the Fazekas scale. Analyses were performed on a subset of participants (n=381) who received baseline [ 18 F]GTP1 tau PET scans. Relationships between WMH, [ 18 F]GTP1 SUVR in an AD‐specific temporal lobe ROI, age, and cognitive scales were assessed graphically and quantified using Pearson correlations, Cohen's D, t‐tests, and multiple linear regression. Result: Tauriel participants had Fazekas scores of zero (n=161), one (n=208), or two (n=12). Per the Figure, participants with Fazekas scores > 0 tended to be older (Cohen's D=0.69, p < 0.001) and have lower temporal [ 18 F]GTP1 SUVR (Cohen's D=0.35, p<0.001). The relationship between temporal [ 18 F]GTP1 SUVR and baseline ADAS‐Cog13 (r=0.39, p<0.001) remained significant after adjusting for Fazekas score and age via multiple regression (p<0.001). Conclusion: Given the circumscribed range of disease severity seen in prodromal‐to‐mild AD participants at screening/baseline in the Tauriel study, the relationships between MRI WMH and [ 18 F]GTP1 tau PET suggest that these pathologies have additive and independent contributions to cognition that may be age‐related. Clinical trials of anti‐tau therapeutics in similar patient populations may need to account for cerebrovascular co‐morbidities in patient selection and/or efficacy analyses.